Key technique of dynamic interface rendering based on device control of smart home App - Tao GUO; Jianting HAN; Xiaoling YANG (Dianxin kexue)
The dynamic interface rendering technology of smart home App was analyzed,and a dynamic interface rendering method based on SWE (smart widget engine) was proposed.Based on an actual case,a smart home App was developed to verify SWE.It shows the method of SWE is a useful exploration for optimization of dynamic interface rendering technology.